..Ok. I understand that a complex number can be written in the form...a+bi.
Which leads me to the idea that
(5-6i)-4i is equivalent to (5-6i)-(0-4i).
The above should be written (5-6i)-4i = (5-6i) - (0 + 4i). Remember, when you put grouping symbols around an expression and precede the group with a negative sign, each sign within the group must be changed to its opposite.
-4i = -(+4i)
Which gives me 5-2i as a solution, because 5-0=5 and -6i-(-4i) is -2i. So.. (5-6i)-4i = 5-2i
Removing the parentheses on the above we get 5 - 6i - 4i = 5 - 10i
Is this a true statement?
My text says no, and I can't wrap my head around it.
P.S. (a+bi)-(c+di)= a+bi-c-di = (a-c)+(b-d)i
Using this, we get (5-6i)-(0+4i) = 5-6i-0-4i = (5-0)+(-6-4)i = 5-10i